Konflikty miejsca urodzenia w „Sońce” Ignacego Karpowicza - Koprowska, Karolina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article aims to present and analyse the concept of “birthplace” which combines different components such as topography, landscape and also cultural, symbolic and metaphorical meanings. The human attitude to a birthplace appears problematic and complex, and involves a need to create a more critical perception of own identity. My theoretical investigation is based on an analysis of Ignacy Karpowicz’s novel “Sońka” which deals with strong tensions between individual experience of the civilians and History of wars and violence, difficult relations between collective and individual identity/memory and their specificity regarding village community, ethnic conflicts connected to the Polish-Belarusian borderland and birthplace, as well.
Conflicts of the birthplace in Ignacy Karpowicz’s novel “Sońka”
Keywords: birthplace; borderland; identity; conflict; village; war; Holocaust; bystander; story; miejsce urodzenia; pogranicze; tożsamość; konflikt; wieś; wojna; Zagłada; postronny obserwator; opowieść